Worldwide basket survey of multielemental composition of white button mushroom Agaricus bisporus - Siwulski, Marek; Budka, Anna; Rzymski, Piotr; Gąsecka, Monika; Kalač, Pavel; Budzyńska, Sylwia; Magdziak, Zuzanna; Niedzielski, Przemysław; Mleczek, Patrycja; Mleczek, Mirosław (Chemosphere, 2020)
Agaricus bisporus is the most commonly cultivated and consumed mushroom species. The aim of this study was to compare the profile of macro- and trace elements in A. bisporus fruit bodies produced commercially in 19 countries in 2018 and distributed worldwide (32 analyzed objects). Trace elements with unknown biological roles were also determined. The content of 36 elements (of 70 taken into account) revealed significant differences among the analyzed objects. Contents of Ca, K, Mg, Na and S varied in wide ranges of 425-2430, 12740-40940, 610-3240, 98-430 and 1030-2650 mg kg-1 dw, respectively. The fruit bodies were characterized by a generally similar content of trace elements with some clear exceptions. Rankings of the objects according to the decreased amount of macroelements, trace elements and all elements jointly, show that mushrooms are significantly diverse as regards the content of particular elements of the mentioned group. The analyzed fruit bodies displayed a relatively high content of Ca, Mo and Se, and a high K/Na ratio. Regardless of origin, A. bisporus did not constitute a source of significant levels of Al, Cd or rare earth elements. An increased level of As and Pb in mushrooms from several producers indicates a need for additional measures to reduce potential dietary exposures to these toxicants.
Keywords: Macroelements; Metal contamination; Global Health; Lead; celosvětové zdraví; Trace Elements; průzkumy a dotazníky; arsen; Trace elements; olovo; Surveys and Questionnaires; stopové prvky; Human exposure; Agaricus; Agaricus bisporus; Arsenic